2008
DOI: 10.1037/1931-3918.2.1.26
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of vicarious trauma among therapist trainees.

Abstract: The current study explored vicarious trauma among therapist trainees in relation to history of trauma, experience level, trauma-specific training, and defense style. Students in graduate clinical and counseling psychology training programs (N ϭ 129) completed the Trauma Symptom Inventory, Defense Style Questionnaire, and an experience questionnaire. Results indicated trauma symptoms were significantly associated with defense style, which appeared to moderate personal trauma history and experience level. Trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
154
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 46 publications
9
154
1
Order By: Relevance
“…Neumann and Gamble (1995) describe Pearlman and McCann's (unpublished) survey of nearly 200 trauma therapists, which found that newer therapists reported more intrusive imagery from the work as well as more anxiety, depression and physical symptoms than did therapists with greater experience. This is consistent with research into the professional development of therapists, indicating that psychological distress is higher for therapists who are less experienced (Adams & Riggs, 2008;Hellman, Morrison, & Abramowitz, 1987;Rodolfa, Kraft, & Reilley, 1988).…”
Section: Impact Of Client Trauma On the Therapy Relationshipsupporting
confidence: 75%
See 2 more Smart Citations
“…Neumann and Gamble (1995) describe Pearlman and McCann's (unpublished) survey of nearly 200 trauma therapists, which found that newer therapists reported more intrusive imagery from the work as well as more anxiety, depression and physical symptoms than did therapists with greater experience. This is consistent with research into the professional development of therapists, indicating that psychological distress is higher for therapists who are less experienced (Adams & Riggs, 2008;Hellman, Morrison, & Abramowitz, 1987;Rodolfa, Kraft, & Reilley, 1988).…”
Section: Impact Of Client Trauma On the Therapy Relationshipsupporting
confidence: 75%
“…This is consistent with research into the professional development of therapists, indicating that psychological distress decreases as therapists become more experienced (Adams and Riggs, 2008;Hellman et al, 1987;Rodolfa et al, 1988). Participants conveyed that through their work with trauma survivors, they had reached a position of acceptance in relation to traumatic occurrences.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A majority of studies fail to reveal significant positive relationships between indirect exposure to client trauma and trauma symptoms (Adams & Riggs, 2008;Badger et al, 2008;Deighton et al, 2007 7 ; Ennis & Horne, 2003;Nelson-Gardell & Harris, 2003;Way et al, 2004). However, all these studies used less precise, more general or longer-term indirect exposure to client trauma measures.…”
Section: Discussionmentioning
confidence: 99%
“…There is only very limited research among trainee psychologists in the area of secondary traumatization; with one published study (Adams & Riggs, 2008) and two doctoral theses (Fama, 2003;Fucci, 2008). Moreover, this research is based in the USA.…”
Section: Contributing Factors To the Development Of Sts And Vt?mentioning
confidence: 99%